Level of motion sickness based on heart rate variability when reading inside a fully automated vehicle - Juffrizal Karjanto; Nidzamuddin Md Yusof; Jacque Terken; Frank Delbressine; Matthias Rauterberg (Universitas Muhammadiyah Magelang, 2022)
This study investigates the level of experienced motion sickness when performing reading while being driven in fully automated driving under three different conditions. One condition was without any intervention while the other two conditions were with the visual (VPIS) and haptic (HPIS) peripheral information system. Both systems provided the upcoming navigational information in the lateral direction three seconds before the turning/cornering was done. It was hypothesized that with the peripheral information systems, the experienced motion sickness would be reduced compared to the condition where a peripheral information system was not present. Eighteen participants with severe motion sickness susceptibility were carefully chosen to undergo the conditions using an instrumented vehicle with the Wizard-of-Oz approach. The participants were required to read from a tablet during the whole 15-minutes of automated driving. Results from the heart rate variability (beats per minute, root means square of successive differences, and high-frequency component) indicated no statistically significant changes (p < 0.05) in motion sickness found with the presence of HPIS and VPIS when performing reading when being driven in automated mode. However, results from this study were mixed and inconclusive, but overall findings indicated mild motion sickness was found in both VPIS and HPIS conditions.